Electricity consumption and economic growth in ASEAN countries / Ahmad Ghazali Ismail - Ismail, Ahmad Ghazali (2016)
The relationship and causality direction between electricity consumption and economic growth is an important issue in the fields of energy economics and policies towards energy use. Extensive literatures has discussed the issue, but the array of findings provide anything but consensus on either the existence of relations or direction of causality between the variables. This study extends research in this area by studying the long-run and causal relations between economic growth, electricity consumption, labor and capital based on the neo-classical one sector aggregate production technology model. The study uses electricity consumption and real GDP measures the economic growth of these countries. These relations are analyzed for ASEAN countries as a whole and also for a group of six ASEAN developing countries. The analysis is conducted using advanced panel estimation approaches. The Westerlund co-integration test and panel Auto Regressive Distribution Lags (ARDL) estimation technique found no long run cointegration in both groups. Results from the panel Granger Causality method found no causality in the short run between energy consumption and economic growth in all ASEAN countries' groups. However, in the long-run, the results indicate that there are bidirectional relationship in group of all ASEAN countries. This study provides supplementary evidences of relationship between electricity consumption and economic growth in ASEAN countries.